Malaysia : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2014)
This Selected Issues paper on Malaysia highlights quantitative assessment of additional measures required during the medium term to achieve fiscal targets. The authorities aim to lower the budget deficit to about 3 percent of GDP by 2015, down from 4.0 percent in 2013, and to balance the budget by 2020. It suggests that ranking fiscal instruments under different fiscal policy goals can help policymakers identify the composition of fiscal adjustment based on their preferences. By combining ranking with the instruments' potential yield helps in identifying the optimal set of measures required to achieve the needed fiscal adjustment.